2019
DOI: 10.1186/s12866-019-1647-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in the gut of wild and mass-reared Zeugodacus cucurbitae and Bactrocera dorsalis revealed by metagenomic sequencing

Abstract: BackgroundInsect pests belonging to genus Bactrocera sp. (Diptera: Tephritidae) pose major biotic stress on various fruits and vegetable crops around the world. Zeugodacus and Bactrocera sp. are associated with diverse bacterial communities which play an important role in the fitness of sterile insects. The wild populations of melon fly, Zeugodacus cucurbitae (Coquillett) and Oriental fruit fly, Bactrocera dorsalis (Hendel) were collected from pumpkin and mango fields, respectively. The laboratory populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…Porphyromonas gingivalis has been shown to increase the metabolic inflammation risk and autoimmune disorders in mice [ 50 ]. Members of the family Flavobacteriaceae were identified in melon flies, Zeugodacus cucurbitae [ 51 ] as well as in the guts of honey bees [ 17 ]. The Flavobacteriaceae_unclassified OTU from this study ( Figure 6 ) was related to Apibacter mensalis , which was isolated from Bombus lapidarius [ 52 ], and Apibacter adventoris isolated from honey bees and bumble bees [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porphyromonas gingivalis has been shown to increase the metabolic inflammation risk and autoimmune disorders in mice [ 50 ]. Members of the family Flavobacteriaceae were identified in melon flies, Zeugodacus cucurbitae [ 51 ] as well as in the guts of honey bees [ 17 ]. The Flavobacteriaceae_unclassified OTU from this study ( Figure 6 ) was related to Apibacter mensalis , which was isolated from Bombus lapidarius [ 52 ], and Apibacter adventoris isolated from honey bees and bumble bees [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Bifidobacterium , Dysgonomonas and family Pseudomonadaceae were found to be predominant only in the hindgut. Dysgonomonas had been identified in many insects’ guts [ 51 , 54 , 55 ]. It is involved in lignocellulose degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota of several insect species have been described to unravel the bacterial communities of the intestinal tract in insects, including Dipteran ( Zeugodacus cucurbitae, Bactrocera dorsalis, Anopheles stephensi , and Aedes albopictus etc. ; Hadapad et al, 2019; Villegas & Pimenta, 2014; Wei et al, 2017), Lepidopteran ( Bombyx mori , and Agrotis segetum etc. ; Chen et al, 2018; Sevim et al, 2010), and Hymenopteran ( Megachile centuncularis, Megaphragma amalphitanum , and different honey bee [ Apis mellifera ] subspecies etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of insect gut microbiota have shown that gut microbiota may vary between insect species, their life stages (Hadapad et al, 2019; Villegas & Pimenta, 2014) or differences in feeding habit, especially for phytophagous insects (Chen et al, 2018; Lim & Ab Majid, 2020; Shelomi et al, 2013). Many studies have indicated that the insect gut microorganisms plays an important role in the development, digestion, metabolism, reproduction, immunity as well as many other physiological functions of their hosts (Chen et al, 2018; Hadapad et al, 2019; Pérez‐Ruiz et al, 2015; Skrodenytė‐Arbačiauskienė et al, 2019). The fact that exogenous bacteria may affect the lifespan of fruit fly ( Drosophila melanogaster ) further implicated the importance of gut microbiota in environmental fitness of the insect host (Brummel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation